ANALISIS WACANA: KAMPANYE THE CENTER OF GENDER STUDIES (CGS) “KESETARAAN GENDER DAN KEBEBASAN PERSPEKTIF ISLAM” MELALUI MEDIA ONLINE - RISKA MUTIAH (Universitas Islam Negeri (UIN) Mataram, 2019)
The new religious movement with a progressive spirit of da’wah is increasing nowadays. They using various social media and website as da’wah channels to reach audiences easily and to campaign their agenda to the public. One of the account of the movement is thisisgender.com belonging to the Center of Gender Studies or CGS. This research examines how the discourse built by CGS as a scientific study group based on the Islamic perspective towards feminism. This research analyzes one of their article “Kesetaraan Gender dan Kebebasan Perspektif Islam” which tend to breaks down gender equality which is considered problematic because the equality between men and women based on social roles in society is considered contrary to the provision of Allah. The text was examined using critical discourse analysis by Norman Fairclough to find out the meaning of the text. Based on the text analysis, the practice of discourse, and social practice, researcher found that the discourse built by the CGS was that Islam was contrary to feminism and gender equality. Through the discourse, the proposition that is are built is that Islamic values and western thought are placed in binary positions.